10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
Melanogenesis, the biological process responsible for melanin synthesis, plays a critical role in determining skin pigmentation and providing photoprotection. Dysregulation of this pathway leads to a wide range of pigmentary disorders that affect a significant proportion of the global population. Traditional approaches to studying melanogenesis rely largely on cultured melanocytes and in vivo animal models; however, these systems present several limitations, including concerns related to physiological relevance, ethical constraints, high maintenance costs, and limited scalability. In recent years, synthetic biology has emerged as a powerful framework for engineering controllable biological systems capable of replicating complex cellular pathways with high precision. Although numerous studies have reported individual synthetic biology approaches for pigment production or pathway engineering, the literature lacks a comprehensive synthesis that integrates these strategies within the broader context of melanogenesis research and its translational potential. This review addresses this gap by consolidating advances in synthetic biology platforms used to investigate and manipulate pigmentation biology. We discuss emerging techniques including genetic engineering, heterologous expression systems, biomimetic constructs, and cell-free assays that enable the reconstruction and modulation of melanin synthesis pathways. These engineered systems allow the development of disease-specific and patient-derived pigmentation models, providing new opportunities for mechanistic studies and personalized therapeutic strategies. Conceptually, this review proposes a unified framework that positions synthetic biology as a versatile toolkit for studying melanogenesis while also enabling scalable production of melanin and melanin-based biomaterials. By bridging developments across molecular engineering, microbial biosystems, and biomimetic technologies, this work highlights how non-conventional systems can transform both fundamental pigmentation research and translational applications in dermatology and biotechnology.